Impacts of industrial water composition on Salicornia in a hydroponic system - Schmitz, Erica Ann (Kansas State University, 2018)
The energy sector needs to transition to renewable energy to provide energy and economic security in the future (Murray & King, 2012). Liquid biofuels are an important renewable fuel in this transition because they are the preferred renewable energy source in the transportation sector (Lange, 2007), and the only renewable energy alternative for the aviation industry [International Air Transport Association (IATA), 2015]. Biofuels produced from food crops (first-generation biofuels) are being produced at an industrial scale, but they create several environmental and social conflicts (Mohr & Raman, 2013). Currently, there is a demand for the next generation of biofuels to resolve the environmental and social conflicts associated with first-generation biofuels. Salicornia, a salt tolerant oil seed crop (Panta et al., 2014), is one feedstock that might be able to resolve some of those conflicts because it can be irrigated with saline water (Warshay et al., 2017). The ability of Salicornia to tolerate saline environments suggests that it might be able to be cultivated in a hydroponic system designed to treat industrial wastewater. A hydroponic system designed to treat industrial wastewater and produce Salicornia as a biofuel feedstock could prevent some of the detrimental effects of industrial sources of saline water on terrestrial and aquatic ecosystems (Gerhart et al., 2006), and produce a feedstock that resolves some of the issues with first-generation biofuels. The first step in the development of the proposed hydroponic system is to determine if Salicornia can be cultivated with industrial wastewater in a hydroponic system. Studies were conducted with two sources of industrial wastewater, Flue Gas Desulfurization (FGD) wastewater and Cooling Tower Blowdown Water (CTBW), to determine how the composition of water affects the germination, survivability, early seedling growth, and lignocellulosic composition of Salicornia. The composition of water was shown to have no effect on seed germination and visual signs of phytotoxicity. These studies found that full strength CTBW and 20% FGD wastewater could be used to cultivate Salicornia in a hydroponic system if nutrients are added. Full strength FGD wastewater was shown to have a negative impact on seedling growth. These studies also found that Salicornia is not a good lignocellulosic biofuel feedstock because of its low lignocellulosic composition (e.g. 14.9-9.1% glucan, 13.2-6.7% xylan, 5.2-2.4% arabinan, and 9.8-6.2% lignin). However, a large percentage of the extractives content is unidentified and could have a monetary value. Additional research is needed to determine if a hydroponic system that cultivates Salicornia is able to provide any water quality treatment.
Keywords: Salicornia; Hydroponic; Industrial Wastewater